2011
DOI: 10.1111/j.1708-8208.2009.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Expectations Before and Evaluation After Dental Implant Therapy

Abstract: Patients' posttreatment completion ratings significantly exceeded their initial expectations. Expectations and posttreatment completion ratings were irrespective of smoking habits, location in the jaw, sex, or educational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
69
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 16 publications
11
69
0
4
Order By: Relevance
“…Previous studies have made a similar evaluation using a variety of questionnaires and scales. 1,2,3,5,8,11,21,22,23 In the present study, high levels of patient satisfaction were found, with no statistically significant difference between genders, which is in agreement with findings described in the literature. 5,9,21,22 Evaluating patients with mandibular overdentures, Pan et al 22 found no statistically significant differences between genders, in regard to comfort, speaking or esthetics.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have made a similar evaluation using a variety of questionnaires and scales. 1,2,3,5,8,11,21,22,23 In the present study, high levels of patient satisfaction were found, with no statistically significant difference between genders, which is in agreement with findings described in the literature. 5,9,21,22 Evaluating patients with mandibular overdentures, Pan et al 22 found no statistically significant differences between genders, in regard to comfort, speaking or esthetics.…”
Section: Discussionsupporting
confidence: 93%
“…However, results based on patient satisfaction are an important aspect in determining treatment success. 1,2 Most studies evaluating the satisfaction of completely edentulous individuals generally compare conventional full dentures to implant-supported prostheses, and report a greater degree of patient satisfaction with the latter. 3,4,5,6,7,8 Other studies also report high degrees of satisfaction among patients with overdentures, regardless of the type of support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expectations that patients have for an implant-supported set are high in contrast to their willingness to make additional payments. Baracat et al 16 compared patients' expectations before implant treatment with their satisfaction regarding function and esthetics after DI therapy. Fifty volunteers answered a questionnaire about influencing variables and underwent an initial examination followed by implant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Awareness about implant treatment procedures among a selected group of patients varies; it was found to be 29% in Finland, 64% in Australia, 72% in Austria, 23.24% of urban Indian populations, 77% in the United States, 66.4% in Saudi Arabia, and 9.7% among health workers in Nigeria. [13][14][15][16][17] In Rustemeyer and Bremerich 1 study, which aimed to evaluate the level of patient knowledge regarding DI, 58% of 315 patients questioned thought that implants require the same care as natural teeth, 80% held the function of an implant-supported overdenture as very important, and 54% attached great importance to the esthetics. The expectations that patients have for an implant-supported set are high in contrast to their willingness to make additional payments.…”
Section: Introductionmentioning
confidence: 99%